Land Conflict Between Companies and The Community in Pari Island, Thousand Islands - Wibisono, Gunawan; Sunarno, Sunarno (Faculty of Law, Universitas Pekalongan, 2024)
This research examines the land conflict that has arisen between a company and the residents of Pari Island in the Thousand Islands. The research addresses the following research questions: 1) What has been the prevailing model for resolving land conflicts between the company and the community of Pari Island in the Thousand Islands up to this point? 2) What is the ideal concept of land ownership and usage envisioned by both the company and the residents of the Thousand Islands? The research employs a sociolegal research methodology. Research Outcomes: 1) The author's analysis suggests that the prevailing approach to resolving land conflicts between the company and the Pari Island community in the Thousand Islands has largely relied on government administration and political conflict resolution, namely